2022
DOI: 10.3390/vaccines10050668
|View full text |Cite
|
Sign up to set email alerts
|

Booster COVID-19 Vaccines for Immune-Mediated Inflammatory Disease Patients: A Systematic Review and Meta-Analysis of Efficacy and Safety

Abstract: Background: Seroconversion and longevity of vaccine-induced immune response is blunted in immune-mediated inflammatory disease (IMID) patients owing to immunosuppressive regimens. COVID-19 booster vaccines after a primary series have been proposed with inconclusive evidence on efficacy to date. Methods: This PROSPERO-registered systematic review (CRD42022302534) was conducted according to PRISMA guidelines. PubMed, EMBASE, CENTRAL, Web of Science, CORD-19, WHO ICTRP, and medRxiv were searched up to 28 February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…General considerations for timing the vaccination chiefly revolve around the return to activities of daily life and restoration of normal blood counts [57]. Overall, similar to other immunocompromised groups receiving immunosuppressive therapy, such as patients with immune-mediated inflammatory diseases and solid organ transplant recipients, booster doses are crucial to afford protection against COVID-19 [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…General considerations for timing the vaccination chiefly revolve around the return to activities of daily life and restoration of normal blood counts [57]. Overall, similar to other immunocompromised groups receiving immunosuppressive therapy, such as patients with immune-mediated inflammatory diseases and solid organ transplant recipients, booster doses are crucial to afford protection against COVID-19 [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that patients on anti-CD20 + therapy had a much lower rate of seroconversion following the booster dose compared to patients receiving non-anti-CD20 + therapy (25% vs 81%). [ 10 ] In our study, approximately one third of the patients who did not initially mount an antibody response to COVID-19 vaccination, were positive after the supplemental dose. This again supports an increase in seroconversion with additional doses, albeit lower than in patients not on RTX.…”
Section: Discussionmentioning
confidence: 62%
“…Another report found that the incidence of adverse events was similar between patients with rheumatic diseases and healthy controls, with a low incidence of flare (<5%) among the former [ 45 ]. A recent meta-analysis on the effect of COVID-19 vaccine booster doses in patients with pre-existing immune-mediated rheumatic diseases found that the incidence of local and systemic adverse events, including disease flares, was either comparable or slightly increased when compared with the primary series of vaccinations [ 46 ]. This information suggests a very low risk of vaccines that might trigger a flare.…”
Section: Discussionmentioning
confidence: 99%